2017
DOI: 10.1080/01443615.2017.1318268
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical bowel preparation for laparoscopic hysterectomy, is it really necessary?

Abstract: In this prospective randomised single-blind case-controlled cohort study the aim was to compare the effects of mechanical bowel preparation (MBP) on field of vision and surgical comfort during total laparoscopic hysterectomy procedures. The study group was made of 102 patients that had undergone total laparoscopic hysterectomy (TLH), between July 2012 and June 2014. Statistical comparison was made between the means of durations of operation between the two groups divided by visual indexing (VI). The patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…There were no differences in intraoperative visualization, bowel handling or overall ease of the operation 16 . Bakay et al, tried to compare the effects of MBP on field of vision and surgical comfort during total laparoscopic hysterectomy, using a more complex Visual Indexing (VI) tool and they reported that the duration of the operation was not affected by the use of MBP and the VI score 17 …”
Section: Discussionmentioning
confidence: 99%
“…There were no differences in intraoperative visualization, bowel handling or overall ease of the operation 16 . Bakay et al, tried to compare the effects of MBP on field of vision and surgical comfort during total laparoscopic hysterectomy, using a more complex Visual Indexing (VI) tool and they reported that the duration of the operation was not affected by the use of MBP and the VI score 17 …”
Section: Discussionmentioning
confidence: 99%
“…Most randomized controlled trials (RCTs) compare oral MBP to no preparation regimen, besides fasting or a type of low residue diet [17][18][19][20][21]. Fewer studies compare oral MBP to enema MBP [11,13].…”
Section: Bowel Preparation Before Minimally Invasive Gynecologicmentioning
confidence: 99%
“…Despite these results, the fasting-only approach was recommended after taking into consideration the distressfulness and the adverse effects of MBP on women [17]. Unlike Won et al, Bakay and Aytekin in 2017 investigated the field of vision and surgical comfort during total laparoscopic hysterectomy procedures in 102 patients, using a visual indexing tool based on anatomic landmarks and found no differences in surgical view or intraoperative time between the group receiving oral MBP and the only 2 e Scientific World Journal [21].…”
Section: Bowel Preparation Before Minimally Invasive Gynecologicmentioning
confidence: 99%
“…Preoperative mechanical bowel preparation (MBP) has been routinely used for gynaecological laparoscopy, hypothetically to improve intraoperative bowel handling and visualization of the operative field [1][2][3][4][5]. The studies investigating the effect of MBP on gynaecological laparoscopy [1,3,[6][7][8][9][10][11] indicate that MBP has little or no benefit on improving the operative field visualization and intraoperative bowel handling. The methods used for the evaluation of those outcomes were subjective in the literature including 4/5/10point Likert scales rated verbally as excellent to poor by the operating surgeons [1,3,6,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the degree of Trendelenburg should be well-adjusted to the minimum where the operative field is adequate to proceed safely. As similar to PP, using a standard TIA throughout the surgical procedure has been a common practice in the literature [1,8,[21][22][23][24]. The TIAs in those studies were usually between 25 • and 40 • and sometimes even steeper depending on the surgical condition that reflects the general practice for adjustments of PP values This study aimed to test the null hypothesis that preoperative MBP does not affect the visualization of the operative field and does not enable lower TIA and PP values at a standardized method of anaesthesia.…”
Section: Introductionmentioning
confidence: 99%